Judetův zadní prístup k lopatce - Bartonícek, J; Tucek, M; Lunácek, L (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2008)
PURPOSE OF THE STUDY: A detailed description of the Judet posterior approach to the scapula. MATERIAL AND METHODS: The authors used this approach in 24 patients operated on for fractures of the scapular body and neck and for combined fractures of the scapula. In 23 patients the surgical site healed without complications, in 1 case revision was required due to a haematoma. DESCRIPTION OF THE APPROACH: The approach has three phases. The first of them consists in a boomerang skin incision along the scapular spine and the medial scapular border producing a skin flap, and identification of the posterior border of the deltoid. In the next phase, the posterior deltoid is dissected off the scapular spine and reflected laterally. In the final phase, the infraspinatus is mobilized and reflected proximally. During the whole procedure the neurovascular bundle passing from the spinoglenoid notch to the infraspinatus must be handled with maximum caution. In certain types of fractures of the scapula, this approach may be limited using a medial and a lateral window to expose the respective borders of the scapular body, without full mobilization of the infraspinatus. On the other hand, where the fracture of the scapula is associated with a fracture of the lateral clavicle or dislocation of the AC joint, the approach may be extended using a saber cut incision starting from the proximolateral angle of the Judet incision and passing over the AC joint. This modification was used in a fracture of the scapular body associated with dislocation of the AC joint. DISCUSSION: The advantage of the Judet approach is an excellent exposure of the infraspinousus fossa. The main disadvantage of this approach is considered its extensiveness and atrophy of the infraspinatus that is most probably caused by its mobilization. However, there may be more causes of this atrophy. The first of them is injury to the suprascapular nerve in fractures of the surgical neck of the scapula by its entrapment in the fracture line. In these fractures the whole course of the nerve in the spinoglenoid notch should be revised. Another cause may be overstretching of the nerve during the operation, when the mobilized muscle is retracted too far proximally, medially or laterally. Therefore a continuous visual control of the nerve is of vital importance. The third cause is inadequate reinsertion of the muscle. A certain role may be played also by insufficient postoperative rehabilitation. Clinical experience gained in the treatment of our patients and a personal experience of one of the authors (injury to the suprascapular nerve during arthroscopy of the shoulder and complete atrophy of the muscle) prove that even after dennervation of the infraspinatus the function of the shoulder is almost normal. Performance of a limited approach using a lateral and a medial window requires sufficient experience in both the Judet approach and internal fixation of the scapula fractures. This modification is indicated in transverse two-part fractures of the scapular body and exceptionally in three-part T- or Y-fractures of the scapular body with a minimal displacement in the vertical fracture line. Its use depends also on the type of the fracture of the lateral border of scapula. Where an interfragment is broken off the lateral border, the fracture line passes close below the glenoid or involves it, the use of a limited approach is questionable. Of great importance in this respect is also the trauma-operation interval. After one week the reduction of the fragments from the limited approach is difficult and there is a potential risk of injury to the suprascapular nerve. An alternative lateral direct approach to the lateral border of the scapula, described for the first time by Dupont and Evrard in 1932, provides only limited exposure and cannot be, where necessary, extended to the entire infraspinous fossa. Therefore it is not suitable for treatment of the scapular body and neck. The posterosuperior approach is indicated in isolated fractures of the posterior glenoid. It uses the horizontal part of the Judet incision and passes along the posterior edge of the acromion and the lateral portion of the scapular spine. After dissection of the spinal and partially the acromial portion of the deltoid off the bone, the muscle can be retracted distally providing access to a more deeply located tendon of the infraspinatus. The tendon may be either retracted or cut and carefully elevated medially thus providing access to the posterior surface of the glenoid and the scapular neck. Where necessary, this approach may be converted to the Judet approach. CONCLUSION: The discussed disadvantages of the Judet approach are relative and its benefits clearly prevail. Therefore it is recommended as the basic posterior approach for operative treatment of fractures of the scapula. Key words: scapula fractures, operative treatment, Judet approach.
Keywords: ortopedické výkony; fraktury kostí; lidé; Scapula; Fractures, Bone; Orthopedic Procedures; lopatka; Humans